Representasi Sosial tentang Kiprah PKS di Panggung Politik Indonesia (Analisis wacana situs dikedaikopi.net) - Dini Safitri (Communicology: Jurnal Ilmu Komunikasi, 2013)
Abstract This study’s objective is to discover social representations of political action performed by elite of PKS (Justice and Prosperous Party) during the party involvement in government, as viewed from its grassroots. Using texts and comments from dikedaikopi.net site, the study also intents at better understanding on how internet-based media is representing critic aimed at authority that was legitimated through religious doctrine. This study also intents to discover what is contained within the representation of wealth in Islamic view as well as its form. The study found that political praxis taken into account by PKS had created series of controversies. The controversies led into some debates within their ranks and grassroots, including on the issue of wealth. Up to now, those debates are controled using religious doctrine of maslahat da’wah (what is favourable for Islamic calling) Keywords : Political Islam, PKS, social representations, internet